Three new species of Neozygina Dietrich & Dmitriev (Hemiptera, Cicadellidae, Typhlocybinae) from Argentina, with a key to South American species - Catalano, María Inés; Paradell, Susana; Dietrich, Christopher H. (Zootaxa, 2013)
Three new species of Neozygina Dietrich & Dmitriev are described from Argentina, N. apicalis sp. nov., N. bifurcata sp. nov. and N. spinula sp. nov. Detailed morphological descriptions and illustrations of the new species are provided, and a key to South American species of the genus is given.